Reducing Botrytis cinerea incidence in unheated tomato greenhouses in real time using a wireless sensors network. - Baptista, F.J. (2012)
The objective was to investigate the influence of ventilation on the humidity conditions in unheated tomato greenhouses and the consequences for Botrytis cinerea control and generate the necessary knowledge to build a warning system for this problem. Two different natural ventilation treatments were randomly assigned to the greenhouses. One treatment was permanent ventilation (PV), with the vents open during the day and night, while the other was classical ventilation (CV), in which the vents were open during the day and closed during the night. On a second stage and supported by a wireless network of air relative humidity and temperature sensors a rules based engine with defined setpoints will be developed to make available a early warning system via SMS, e- mail and Web. This will allow the growers to act only when needed, making possible to reduce chemical use, lowering both production costs and environmental impacts.